Analisis Yuridis terhadap Putusan Hakim yang Menyatakan Tuntutan Penuntut Umum Tidak dapat Diterima dalam Perspektif Due Process of Law: Studi Putusan PN Oelamasi No. 1/Pid.Sus-Anak/2020/PN Olm - Dedi Polin; Simpexius Asa; Orpa Ganefo Manuain (Student Scientific Creativity Journal, 2026)
A decision declaring a public prosecutor’s indictment inadmissible (niet ontvankelijke verklaard) is an interesting phenomenon in Indonesian criminal justice practice because it is not explicitly regulated as a final judgment under the Criminal Procedure Code. This study aims to analyze the legal reasoning of judges in rendering a decision declaring the prosecutor’s indictment inadmissible in Decision of the Oelamasi District Court Number 1/Pid.Sus-Anak/2020/PN Olm and to examine its juridical implications for the juvenile criminal justice system. This research employed a normative legal method using statutory, conceptual, and case approaches. Legal materials were collected through library research consisting of primary, secondary, and tertiary legal sources and were analyzed qualitatively. The findings reveal that the judges’ reasoning was based on a fundamental procedural defect during the investigation stage, namely the absence of mandatory assistance from parents or guardians, community counselors, and legal counsel as required under Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Such violation rendered the investigation process legally defective and consequently affected the validity of the prosecution. The decision emphasizes the importance of implementing the principles of due process of law, child protection, and procedural legality within the juvenile criminal justice system. Therefore, stronger regulations and supervisory mechanisms are required to ensure legal certainty and the protection of children’s rights throughout the criminal justice process.